Percutaneous closure of an iatrogenic right ventricular perforation with an angio-seal vascular closure device: a case report. Issue 5 (21st August 2020) - Coughlan, J J; Szirt, Richard; Pearson, Ian; Cosgrave, John
Abstract: Background: Iatrogenic perforation of the right ventricle (RV) is a rare but recognized complication of pericardiocentesis. Treatment strategies for RV perforation include surgical repair and percutaneous closure. In this case report, we describe the use of an angio-seal vascular closure device (Terumo Interventional Systems) to seal an iatrogenic RV perforation secondary to incorrect placement of a pericardial drain. Case summary: A 55-year-old female presented with an anterior ST-elevation myocardial infarction. Coronary angiography demonstrated occlusion of the left anterior descending artery. The patient went on to have primary percutaneous coronary intervention and both the left anterior descending and D1 were wired. During kissing balloon inflation, the Sion Blue wire migrated distally in the D1 causing an Ellis type 3 wire tip perforation in the distal D1. Emergency pericardiocentesis was performed however the 8 French (8 Fr) pericardial drain was inadvertently inserted into the RV. It was decided to attempt percutaneous closure with an 8 Fr angio-seal in the catheter lab under echocardiographic and fluoroscopic guidance. Our patient did not demonstrate any recurrence of pericardial effusion on repeat echocardiography over 60 days post-procedure. Discussion: Our patient did not demonstrate any recurrence of pericardial effusion on repeat echocardiography over 60 days post-procedure. We feel that the angio-seal vascular closure device represents an effective, minimally invasive treatment for this rare but potentially catastrophic complication of pericardiocentesis. In this case, the technique spared our patient a sternotomy with its associated morbidity.